Effect of sowing dates and zinc foliar on the productivity of some sunflower cultivars at New Valley - Abd El-Iateef, A. A. (2012)
Two field experiments were carried out in the Desert Research Center (D.R.C.), Agricultural Experimental Station at El- Kharga, New Valley Governorate, during two summer seasons of 2010 and 2011. These experiments aimed to study yield and its components, oil percent (%), and oil yield at planted three dates, three sunflower varieties as affected by three zinc foliar application treatments. A split - split plot design with four replicates was used, where sowing dates devoted to the main plots, sunflower varieties allocated in the sub plots, and zinc foliar treatments arranged in the sub - sub plots. The obtained results could be summarized as follows: Tenth of August planting date gave the highest values for plant height (cm.), head diameter (cm.), number of seed / head, head seed weight (g.), 100- seed weight (g.), seed yield (kg/fad.), Stover yield (kg/fad.), oil content (%) and oil yield (kg/fad.) of sunflower varieties. Sunflower variety Hy sun 333 showed superior its over Sakha 53 and Giza 102 varieties in all studied traits. Zinc foliar treatment of 0.06% as zinc sulphate treatment gave the highest values over the control (tap water) for all studied traits. The first and second order interactions had significant effects on all studied traits.
Includes reference.
Summary in Arabic.
1
Keywords: Sunflowers -- Sowing; Sunflowers -- Varieties; Foliar feeding; Zinc in agriculture